Study the Impact of the Distance Factor on the Optimal Workable Frequencies for the Long Distance Radio Communications - A. Nasser, Randa; A. Hadi, Khalid (Iraqi Journal of Science, 2023)
In this research, the influence of the distance factor on the optimal workingfrequency (FOT) parameter has been studied theoretically for the ionosphere layerover the Middle East Zone. The datasets of the (FOT) parameter have beengenerated using the (VOACAP) model which considers as one of the recommendedmodern international communication models that used to calculate the ionosphereparameters. The calculations have been made for the connection links between thecapital Baghdad and many other locations that distributed on different distances anddirections over the Middle East region. The years (2011-2013) of the solar cycle 24have been adopted to study the influence of the distance factor on the FOTparameter. The results of the conducted study showed that the distance factor has aclear influence on the values of the FOT parameter, also the day/night effect is moresignificant in the long distance HF links (i.e. more than a 500 Km).